Three-Dimensional Extracellular Matrix Scaffolds by Microfluidic Fabrication for Long-Term Spontaneously Contracted Cardiomyocyte Culture - Mei, Jeng-Chun (Tissue Eng Part A, 2014)
To repair damaged cardiac tissue, the important principle of in vitro cell culture is to mimic the in vivo cell growth environment. Thus, micro-sized cells are more suitably cultured in three-dimensional (3D) than in two-dimensional (2D) microenvironments (ex: culture dish). With the matching dimensions of works produced by microfluidic technology, chemical engineering and biochemistry applications have used this technology extensively in cellular works. The 3D scaffolds produced in our investigation has essential properties, such has high mass transfer efficiency, and variable pore sizes, to adapt to various needs of different cell types. In addition to the malleability of these innovative scaffolds, fabrication procedure was effortless and fast. Primary neonatal mice cardiomyocytes were successfully harvested and cultured in 3D scaffolds made of gelatin and collagen. Gelatin and gelatin–collagen scaffold were produced by the formation of microbubbles through a microfluidic device, and the mechanical properties of gelatin scaffold and gelatin–collagen scaffold were measured. Cellular properties in the microbubbles were also monitored. Fluorescence staining results assured that cardiomyocytes could maintain in vivo morphology in 3D gelatin scaffold. In addition, it was found that 3D scaffold could prolong the contraction behavior of cardiomyocytes compared with a conventional 2D culture dish. Spontaneously contracted behavior was maintained for the longest (about 1 month) in the 3D gelatin scaffold, about 19 days in the 3D gelatin–collagen scaffold. To sum up, this 3D platform for cell culture has promising potential for myocardial tissue engineering.